2017
DOI: 10.1111/polp.12206
|View full text |Cite
|
Sign up to set email alerts
|

A Birther and a Truther: The Influence of the Authoritarian Personality on Conspiracy Beliefs

Abstract: I find that 10 percent of Americans believe in both “trutherism” and “birtherism.” Even among citizens who say they like Bush or Obama, or are from the same party, many still believe in conspiracies implicating the presidents. It is crucial to understand why so many Americans believe obviously erroneous conspiracies that denigrate a president who otherwise has their support. I predict that the authoritarian personality creates a predisposition to believe in conspiracies based on the tendency of those high in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 42 publications
3
32
3
Order By: Relevance
“…Political extremism, either to the left or to the right, is associated as an attempt or thinking style, aimed at, once again, making sense of societal events (van Prooijen et al, 2015). Additionally, right-wing authoritarianism was a positive predictor—a political attitude characterized by obedience to an authoritarian leader, a deeply rooted mentality when it comes to traditional societal values, and, at the same time, a distrust against governmental structures (Imhoff and Bruder, 2014; Richey, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Political extremism, either to the left or to the right, is associated as an attempt or thinking style, aimed at, once again, making sense of societal events (van Prooijen et al, 2015). Additionally, right-wing authoritarianism was a positive predictor—a political attitude characterized by obedience to an authoritarian leader, a deeply rooted mentality when it comes to traditional societal values, and, at the same time, a distrust against governmental structures (Imhoff and Bruder, 2014; Richey, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For example, generalized interpersonal mistrust is significantly associated with some types of conspiracy beliefs, but not others (Oliver & Wood, 2014a). Mistrust in government has been found to be associated with general conspiracist ideation and political conspiracy theories Richey, 2017), but not conspiracy theories related to other themes (van Prooijen & Acker, 2015).…”
Section: Component 1: Epistemic Mistrustmentioning
confidence: 96%
“…Some studies support this assumption (Galliford & Furnham, ; Miller et al, ). Furthermore, several studies (e.g., Bruder et al, ; Grzesiak‐Feldman & Irzycka, ; see also Richey, ) reported a link between conspiracy beliefs and right‐wing authoritarianism—a dimension of political attitudes characterized by preference for conventionalism, authoritarian aggression, and authoritarian submission to authorities (Altemeyer, ). On the other hand, Oliver and Wood () and Uscinski and Parent () did not find a link between political ideology/party and conspiracy belief, and Berinsky () did not find a link between authoritarianism and conspiracy belief.…”
Section: Definitionsmentioning
confidence: 99%